A Status-enhancement account overconfidence. [article]. - Anderson, Cameron
In explaining the prevalence of the overconfident belief that one is better than others,prior work has focused on the motive to maintain high self-esteem, abetted by biases in attention, memory, and cognition. An additional possibility is that overconfidence enhances the person's social status. We tested this status-enhancing account of overconfidence in 6 studies. Studies 1-3 found that overconfidence leads to higher social in both short-and longer-term groups, using naturalistic and experimental designs. Study 4 applied a Brunswikian lens analysis (Brunswik, 1956) and found that overconfidence leads behavioral signature that makes the individual appear competent to others. Studies 5 and 6 measured and experimentally manipulated the desire for status and found that the status motive promotes overconfidence. Together, these studies suggest that people might so often believe they are better than others because it helps them achieve higher social status. - (from the authors).